Electromyography evaluation of masseter and temporalis muscles in patients with temporomandibular joint dysfunction - Noorali, Dr. Imad S.; Baheer, Dr. Majeed A. (Mustansiria Dental Journal, 2019)
Aim: Temporomandibular disorders (TMD) are composed of heterogeneous masticatory disorders which include muscle and joint disorders, Major precipitating factors are occlusal, traumatic, psychosocial and systemic factors. The symptoms associated with this syndrome are due to hyper function and/or dysfunction of the masticatory muscles, rather than to degenerative or inflammatory changes of the TMJ. Various attempts have been made to demonstrate this hyperactivity via EMG recordings of the masticatory muscles. The aim of this investigation was to determine possible altered muscular function in patients with TMD, as well as to determine the need for EMG application in TMD diagnosis. Methods: Thirty adults participated in this study: 20 subjects with signs and symptoms of TMD and 10 asymptomatic subjects. Surface EMG recordings were obtained from left and right anterior temporal muscle, left and right masseter muscle. Results: of this investigation showed the presence of altered masticatory muscle activity in TMD patients and confirmed the use of electromyography in TMD diagnosis. Conclusion: The investigation has confirmed that EMG is a useful and non-invasive method in TMD diagnosis.